Functional roles of Ca(v)1.3(alpha(1D)) calcium channels in atria insights gained from gene-targeted null mutant mice - Zhang, Z; He, YX; Tuteja, D; Xu, DY; Timofeyev, V; Zhang, QA; Glatter, KA; Xu, YF; Shin, HS; Low, R; Chiamvimonvat, N (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Background - Previous data suggest that L-type Ca2+ channels containing the Ca(v)1.3(alpha(1D)) subunit are expressed mainly in neurons and neuroendocrine cells, whereas those containing the Ca(v)1.2(alpha(1C)) subunit are found in the brain, vascular smooth muscle, and cardiac tissue. However, our previous report as well as others have shown that Ca(v)1.3 Ca2+ channel - deficient mice (Ca(v)1.3(-/-)) demonstrate sinus bradycardia with a prolonged PR interval. In the present study, we extended our study to examine the role of the Ca(v)1.3(alpha(1D)) Ca2+ channel in the atria of Ca(v)1.3(-/-) mice. Methods and Results - We obtained new evidence to demonstrate that there is significant expression of Ca(v)1.3 Ca2+ channels predominantly in the atria compared with ventricular tissues. Whole-cell L-type Ca2+ currents (I-Ca,I-L) recorded from single, isolated atrial myocytes from Ca(v)1.3(-/-) mice showed a significant depolarizing shift in voltage-dependent activation. In contrast, there were no significant differences in the ICa, L recorded from ventricular myocytes from wild-type and null mutant mice. We previously documented the hyperpolarizing shift in the voltage-dependent activation of Ca(v)1.3 compared with Ca(v)1.2 Ca2+ channel subunits in a heterologous expression system. The lack of Ca(v)1.3 Ca2+ channels in null mutant mice would result in a depolarizing shift in the voltage-dependent activation of ICa, L in atrial myocytes. In addition, the Ca(v)1.3-null mutant mice showed evidence of atrial arrhythmias, with inducible atrial flutter and fibrillation. We further confirmed the isoform-specific differential expression of Ca(v)1.3 versus Ca(v)1.2 by in situ hybridization and immunofluorescence confocal microscopy. Conclusions - Using gene-targeted deletion of the Ca(v)1.3 Ca2+ channel, we established the differential distribution of Ca(v)1.3 Ca2+ channels in atrial myocytes compared with ventricles. Our data represent the first report demonstrating important functional roles for Ca(v)1.3 Ca2+ channel in atrial tissues.
Keywords: CA2+ CHANNELS; PACEMAKER ACTIVITY; SINOATRIAL NODE; MOUSE; FIBRILLATION; EXPRESSION; ALPHA(1D); IDENTIFICATION; SUBUNITS; MUTATION